Development of a Chiral Capillary Electrophoresis Method for the Enantioseparation of Verapamil Using Cyclodextrins as Chiral Selectors and Experimental Design Optimization - Melania Cârcu-Dobrin (MDPI AG, 2021)
Chirality is a property of asymmetry which determines the pharmacokinetic and pharmacological profiles of optically active pharmaceuticals. Verapamil (VER), a calcium channel blocker phenylalkylamine derivative used in the treatment of cardio-vascular diseases, is a chiral compound, marketed as a racemate, although differences between the pharmacokinetic and pharmacological attributes of the enantiomers have been reported. The aim of our study was to develop a new chiral separation method for VER enantiomers by capillary electrophoresis (CE) using cyclodextrins (CDs) as chiral selectors (CSs). After an initial screening, using different native and derivatized CDs, at four pH levels, heptakis 2,3,6-tri-O-methyl-β-CD (TM-β-CD), a neutral derivatized CD, was identified as the optimum CS. For method optimization, a preliminary univariate approach was applied to characterize the influence of analytical parameters on the separation followed by a Box–Behnken experimental design to establish the optimal separation conditions. Chiral separation of enantiomers was achieved with a resolution of 1.58 in approximately 4 min; the migration order was R-VER followed by S-VER. The method analytical performance was evaluated in terms of precision, linearity, accuracy, and robustness (applying a Plackett–Burnam experimental design). The developed method was applied for the determination of VER enantiomers in pharmaceuticals. Finally, a computer modelling of VER–CD complexes was used to describe host–guest chiral recognition.